. effect of fertilizer insertion in the harvested mother banana plant pseudostem (musa aaa simmonds) (2013)
The need for more efficient nutrient use in adverse conditions, such as droughts, facilitated the development of new alternatives for fertilizer application, such as direct insertion into the vascular system of the pseudostem of harvested banana plants (Musa AAA Simmonds), considering the plant interconnection between the mother plant and the sucker in succession. The objective of this study was to evaluate the effect of fertilizer insertion into the pseudostem of banana plants compared to the conventional soil fertilization system. The study was conducted at two locations (north and center of Urabá region), setting different rates of fertilizer treatments (75, 100 and 125% of the commercial rate) inserted at different heights (0.6 m and 0.9 m) with a soil application of fertilizers as a control treatment. Biometric (height, pseudostem diameter, number of leaves), physiological (specific leaf area and specific leaf weight), and production variables were evaluated in the plants. According to the results, it was evident that the 0.9 m insertion height of the fertilizer was better than 0.6 m and the soil application. Al- though no significant differences were found between doses of fertilizer, we observed a trend of better performance for plants in treatments of 75% and 100% fertilizer dose inserted at 0.9 m.